‫اﻟﺘﻤﻮﻳﻞ‬‫ﻏﻴﺮ‬ ‫اﻟﺘﻘﻠﻴﺪي‬ ‫ﺑﻴﻦ‬ ‫ﺗﺪﻧﻲ‬ ‫ﻗﻴﻤﺔ‬ ‫اﻟﻌﻤﻠﺔ‬ ‫وﺗﻔﺎدي‬ ‫ﻋﺠﺰ‬ ‫اﻟﺨﺰﻳﻨﺔ‬ ‫اﻟﻌﻤﻮﻣﻴﺔ‬ ‫‪‬‬‫دراﺳﺔ‬‫ﺗﺤﻠﻴﻠﻴﺔ‬ ‫ﻟﺤﺎﻟﺔ‬ ‫اﻟﺠﺰاﺋﺮ‬ ‬‬ - ‬‫ﻋﺒﺪ‬ ‫اﻟﺤﻖ‫ ﻛﺒﻴﺮ‬ (My University, 2018)
The aim of this study aims to know the central bank through its policy, its revenues and its public expenditure, the policy of reduction of the national currency on the one hand and on the other hand the unconventional financing through its definition, its functions, its objectives, the difference between reduction and devaluation of national currency, In my study, I analyzed various variables macroeconomic, examined the effect of non-financing conventional on Algeria and how non-financing conventional can bring Algeria out of this crisis without resorting to external debt.